Informatics driven quality improvement in the modern histology lab. Issue 4 (30th November 2020) - Seifert, Robert P; Casler, Vektra; Al Qaysi, Nada; Gothi, Shaileshbhai Revabhai; Williams, Leah; Christensen, Patricia R; Flax, Sherri; Chamala, Srikar
Abstract: Laboratory Information Systems (LIS) and data visualization techniques have untapped potential in anatomic pathology laboratories. Pre-built functionalities of LIS do not address all the needs of a modern histology laboratory. For instance, "Go live" is not the end of LIS customization, but just the beginning. After closely evaluating various histology lab workflows, we implemented several custom data analytics dashboards and additional LIS functionalities to monitor and address weaknesses. Herein, we present our experience in LIS and data-tracking solutions that improved trainee education, slide logistics, staffing/instrumentation lobbying, and task tracking. The latter was addressed through the creation of a novel "status board" akin to those seen in inpatient wards. These use-cases can benefit other histology laboratories.